Source code associated with "Shear-parallel tropical convective systems: importance of cold pools and wind shear" - Grant, Leah D.; Moncrieff, Mitchell W.; Lane, Todd P.; van den Heever, Susan C. (Colorado State University. Libraries, 2020)
The impact of cold pools on line-orientated convective systems is assessed using idealized simulations of tropical oceanic convection under weak, moderate, and strong wind shear regimes. Cold pools are weakened by suppressing evaporation in the shallow sub-cloud layer. Analysis of objectively-identified convective systems reveals that the convection with weaker cold pools is more often oriented parallel, rather than perpendicular, to the wind shear. The cold pool-induced orientation changes are most pronounced in the strong shear environment. Interactions between convective orientation and the tropical atmosphere are assessed. Simulations with shear-parallel convection demonstrate more top-of-atmosphere upwelling longwave radiation and less reflected shortwave radiation due to changes in convective anvils, faster-propagating larger-scale gravity waves, narrower cross-shear moisture distributions, and differences in convective momentum fluxes. The results highlight critical interactions across convective scales, mesoscales, and climate scales, as well as avenues for parameterizing structural modes of mesoscale-organized convection in global models.
This dataset contains source code for the RAMS model simulations and Matlab analysis documented and described in the associated publication, "Shear-Parallel Tropical Convective Systems: Importance of Cold Pools and Wind Shear."
Department of Atmospheric Science
Keywords: tropical convection; shear parallel convection; cold pools; wind shear; idealized model; cloud resolving model